2013
DOI: 10.1080/01635581.2012.725194
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Quercetin in Combination Have Anticancer Activity in Colon Cancer Cells and Repress Oncogenic microRNA-27a

Abstract: Resveratrol and quercetin (RQ) in combination (1:1 ratio) previously inhibited growth in human leukemia cells. This study investigated the anticancer activity of the same mixture in HT-29 colon cancer cells. RQ decreased the generation of reactive oxygen species (ROS) by up to 2.25-fold and increased the antioxidant capacity by up to 3-fold in HT-29 cells (3.8-60 μg/mL), whereas IC50 values for viability were 18.13, 18.73, and 11.85 μg/mL, respectively. RQ also induced caspase-3-cleavage (2-fold) and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 44 publications
4
77
0
Order By: Relevance
“…Likewise, in plant extracts, synergistic bioactive effects between polyphenolics can occur. Del Follo-Martinez et al (2013) reported that resveratrol and quercetin in combination had increased anticancer activity in colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in plant extracts, synergistic bioactive effects between polyphenolics can occur. Del Follo-Martinez et al (2013) reported that resveratrol and quercetin in combination had increased anticancer activity in colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the importance of energy restriction employment in CRC [25,26] . Resveratrol is one of the compounds that have successfully changed the clinical course of patients with CRC through various mechanisms, including energy restriction [27][28][29] . On the other hand, OSU-CG5, by eliciting starvation-associated cellular responses through glucose uptake inhibition, has demonstrated a therapeutic value in targeting prostate cancer cells [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of resveratrol and quercetin were observed to increase anticancer activity in colon cancer cells (Del Follo-Martinez et al, 2013).…”
Section: Dpph Abtsmentioning
confidence: 99%